Pemberdayaan Ibu-Ibu Rumah Tangga Dalam Pengembangan Usaha Makanan Kerupuk Beras Sebagai Ekonomi Kreatif Di Dukuh Sumurgung Desa Pucangrejo Kecamatan Sawahan Kabupaten Madiun - Hadin Sri Isnaini; Dwi Setya Nugrahini (IAI Darussalam, 2022)
Empeworment activities are used to facilitate local people in their planning, to decide and manage local resources to make them have the ability to make sustainable use of upholstery. Potential in the village of Pucangrejo in one of the rice plants. Seeing that potential I plan to make processed rice out of rice. This food can be described as rice cracker, developed in various shapes and flavors. The creative economy is a concept to realize sustainable economic development creatively based, in this case a dependable creative human resource. The creative economy is one of the concepts of a new economy tht intensifies information and generated from this creative economy is a product that has distinctive, unique and unique characteristics. The village’s creative economy was converted to developing and improving the economy of the people with a contribution of the special people of puherreio village housewives is expected to have this activity well under way and can help the development of resources.